Analysis of Bumdes Health Based on Marketing Aspects and Financial Aspects - Achmad Hasan Hafidzi; Ibna Kamilia Fiel Afroh (Manajemen Bisnis, 2022)
This study aims to analyze the health of Bumdes based on marketing and financial aspects (Case Study of BUMDes Dukuh Dempok, Wuluhan District, Jember Regency). The research design used in this research is descriptive research with a quantitative approach. The population of this study is population used in this study are all consumers of Bumdes Dukuh Dempok products in Jember Regency. the method used in this research is purposive sampling. The number of samples in this study was 65 respondents. The data analysis method used in this study is the Structural Equation Model (SEM). The results showed that Brand Personality on Brand Love showed a significant positive effect. Brand Personality on Brand Loyalty shows a significant positive impact. Brand Love on Brand Loyalty shows a significant positive effect. Brand Love plays a role in mediating the influence of Brand Personality on the Brand Loyalty of BUMDes Dukuh Dempok products. Based on the capital ratio at BUMDes Dukuh Dempok, Wuluhan District, the financial aspect is classified as excellent and appropriate.